MARIANISMO E ICONOGRAFIA NOS PRIMÓRDIOS DA IGREJA CATÓLICA: A ANUNCIAÇÃO À VIRGEM MARIA - Baptista, Anna Paola P. (PHOÎNIX, 2020)
This paper studies the iconography of Mary as the virgin mother of God, especially the scenes referring to the Annunciation by the angel, those images being related to theological standpoints adopted at different times by the Church. The period thus covered begins at the fourth century and ends at the twelfth.